P806 Impact of patient age, gender and season of admission on length of stay in hospital for acute inflammatory bowel disease admissions. (25th January 2019) - Yadav, A; Unal, M; Armstrong, P R; Fauzi, M N; Tony, A; McGarry, C; Shaw, C; Hall, B; Kelly, O; Smyth, C; Farrell, R J
Abstract: Background: There has been increased emphasis on predicting Estimated Date of Discharge (EDD) for patients admitted to acute Irish public hospitals. Several factors including age and gender has been associated with prolonged hospital admissions. Environmental factors also play a role in exacerbations of inflammatory bowel disease. To the best our knowledge there has been no such study that assessed the role of age, gender and seasons in predicting length of stay (LOS) in patients admitted with acute exacerbations of IBD. The aim of this study was to determine whether age, gender or season of admission could be used as predictor for Length of stay for patients admitted to acute hospital with exacerbations of IBD. Methods: This single-centre retrospective cohort study included patients admitted acutely to our hospital with exacerbation of Crohn's disease (CD) and Ulcerative colitis (UC) between January 1st 2015 and August 31st 2018. Patient data were accessed from Hospital In-Patients Enquiry (HIPE) system. The mean length of stay was correlated with gender, month of admission and different age groups. The data were analysed using IBM-SPSS software. Results: A total of 266 patients were included in the study. CD: 168 (M: 81, F: 87, Mean age: 41 ± 15.3 years), UC: 98 (M: 39, F: 59, Mean age: 51.14 ± 21.07 years). For CD, the mean LOS for males and females was 6.70 days and 5.86 days, respectively ( p = 0.180, t-test). For UC, the mean LOS for males and females was 6.82 days and 5.51 days, respectively ( p = 0.778, t-test). In CD, the mean LOS for age groups < 35 years, 35–55 years and >55 years was 6.1 days, 6.4 days, and 6.5 days, respectively ( p = 0.91, one-way Innova test). In UC, the mean LOS for age groups < 35 years, 35–55 years and >55 years was 6.1 days, 4.7 days, and 6.5 days, respectively ( p = 0.36, one-way Innova test). In CD, the mean LOS for seasons spring, summer, autumn and winter was 5.6 days, 6.3 days, 6.1 days and 6.9 days, respectively ( p = 0.78, one-way Innova test). In UC, the mean LOS for seasons spring, summer, autumn and winter was 6.4 days, 5.5 days, 6.9 days and 5.4 days, respectively ( p = 0.65, one-way Innova test). Conclusions: Our data indicate that there is no significant correlation between age, gender and season of admission when compared with mean length of stay. Elderly population has higher co-morbidities, which lengthens their hospital stay; however, younger patients with IBD may have more aggressive disease and this results in almost similar length of stay in both patient groups.